Membangun Iklim Organisasi Melalui Peran Kepala Madrasah dalam Upaya Meningkatkan Motivasi Kerja di MIN 1 Ponorogo - Nazula, Desy (Addabani: Interdisciplinary Journal of Islamic Education, 2024)
Motivation is a crucial element that drives enthusiasm for a teacher’s work. However, a decrease in motivation can result in a lack of enthusiasm for learning innovation, with the impact mainly felt by students through monotonous and less varied learning. As a leader, the principal is expected to play a vital role in building and maintaining teacher motivation. This research uses a descriptive qualitative approach focusing on the organizational climate and the role of the madrasa head in increasing teacher work motivation at MIN 1 Ponorogo. This research aims to determine the madrasa headâ€™s role in increasing teacher motivation. The research results show that an excellent organizational climate, mainly through democratic leadership, positively impacts teacher performance. The madrasa head at MIN 1 Ponorogo is influential in providing motivation, involving teachers in decision-making, and creating a collaborative work environment.